Development of Webtoon-Based E-Comics as a Learning Media for Indonesian Flora and Fauna with Enjoy Learning Aprroach - Prinandari, Ajeng Ayu; Sahrina, Alfi; Purwanto (Future Space: Studies in Geo-Education, 2024)
The 21st-century educational landscape necessitates integrating technology into learning. This study highlights a gap in current learning media, overly reliant on traditional textbooks, and failing to fully engage students. To address this, the research proposes the development of webtoon-based e-comic media focused on Indonesian Flora and Fauna, aiming to create a more engaging and effective learning experience. This research utilizes the 4D model by S. Thiagarajan for media development, encompassing four distinct phases: 1) Define, 2) Design, 3) Develop, and 4) Disseminate. The study's participants include students from class XI IPS 1 and a geography teacher at SMAN 1 Gambiran, Banyuwangi. The research employs qualitative descriptive analysis for data evaluation. The findings of the material and media validation process yielded a score of 77.7%, categorizing it as highly appropriate or valid. Furthermore, the implementation of this media in an educational setting was assessed, revealing that teachers found the media 91.3% effective, while student receptivity was even higher at 93.2%. These results underscore the suitability of the webtoon-based e-comic as a learning medium. The positive reception from both students and teachers indicates its potential as an engaging educational tool, enhancing knowledge acquisition in the field of Indonesian Flora and Fauna